GRID-system Based on European EGI Standards for Large-scale Calculations Using the Original Accelerated Method of Quantum Chemistry - Nikolay A. Anikin; Alexander Y. Muskatin; Mikhail B. Kuzminsky; Alexandr I. Rusakov (Моделирование и анализ информационных систем)
Based on the analysis of modern tools for creating GRID-type information systems that are part of the European EGI “standard” – UMD repository (including new versions of Globus Toolkit, ARC, dCache, etc.), the applying of GRID systems for computational chemistry is briefly discussed. The GRID system created by the authors combines two clusters with Linux CentOS 7 and is based on software from UMD-4. The relevance and effectiveness of batch processing systems (we use Torque 4.2.10) in quantum chemical calculations is increased for mass calculations of docking complexes (including for drug modeling problems), for which an improved semiempirical method with more efficient approximations was proposed, implemented in the Fortran-95 LSSDOCK software package. For such calculations, new approximation methods have been developed, including for DFT functionals, and their software implementation is carried out. Converters of calculation results by LSSDOCK into a natural for GRID XML-based format CML version 3 are developed. Using the CML format based on dCache software, a single tree of a virtual GRID filesystem distributed between heterogeneous nodes is used to store the results of LSSDOCK calculations.